APLIKASI BERBASIS ANDROID UNTUK PENJADWALAN KEGIATAN PONDOK PESANTREN MENGGUNAKAN KODULAR - Devi Astri Nawangnugraeni; M Zakki Abdillah; Akrim Teguh Suseno; Achmad Dimyati; Daroji Daroji; Laily Amalia (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2023)
Implementation of information systems is currently needed in all areas of life such as economics, social, health and education. One of the uses of information systems in the field of education is to assist in managing the schedule of activities at Islamic boarding schools. Some Islamic boarding schools currently still use the manual method of scheduling activities, such as recording in the agenda book and the delivery of activity information still uses the bulletin board. This causes the possibility of redundancies of activities and activity information being delivered late. So an application system was developed to assist in managing scheduling at Islamic boarding schools. The application is designed using Unified Modeling Language (UML) and developed using Kodular tools. The results of the development are then tested using blackbox testing, the results that all menus and features in the application are running according to the performance flow, there are no errors and bugs and according to the needs of the Islamic boarding school. So that the application can be used to assist in managing the scheduling system at Islamic boarding schools effectively and efficiently.